Impact and Forms of Bureaucratic Politicization in the 2020 Barru Regency Regional Head Election - Mujiburrahman Mujiburrahman; Jagdish S Joshi; Widya Astuti; Merina Afrilia (JGov: Journal of Governmentality, 2025)
This study addresses the issue of bureaucratic politicization in regional head elections, a phenomenon that challenges the neutrality of the State Civil Apparatus (ASN) and threatens the quality of democracy in Indonesia. Using the theoretical perspective of patron–client relations and bureaucratic neutrality, this research explores how and why ASN becomes politically involved in the 2020 simultaneous regional head election in Barru Regency. The study applies a qualitative approach with descriptive analysis to obtain an in-depth understanding of bureaucratic involvement. The findings reveal that the bureaucracy was politicized through covert roles in success teams, the mobilization of subordinates, and the utilization of kinship networks to support particular candidates. The factors driving this involvement include a strong patron–client culture, political intervention, and position-oriented motivations. This condition not only weakens the principles of bureaucratic neutrality but also creates potential risks for the reproduction of corrupt practices in local governance. The study contributes to the discourse on bureaucratic neutrality in electoral politics and offers insights for strengthening democratic institutions in Indonesia.